User-Centered Design Approaches to Enhance Employee Attendance Applications - Wahyu Maulana Prawiro; Egia Rosi Subhiyakto (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
In the current digital era, Human Resource Management (HRM) has undergone significant transformation with the advent of technology, including employee attendance applications. These applications replace inefficient and error-prone manual methods, facilitating effective attendance, leave, and monitoring of working hours. This study aims to apply a user-centered design (UCD) approach to developing an employee attendance application to enhance user experience (UX). Evaluation using the System Usability Scale (SUS) revealed a usability score of 86.37, classified as